IMPORTANCE OF DISTANCE EDUCATION TECHNOLOGY IN PRIMARY EDUCATION - Onakhon Jabborova; Dinorakhon Saparbayeva (European Science Publishing, 2024)
The article discusses the importance of distance learning technology in primary education and presents the author's approach.
Keywords: primary education, distance education, technology and approach, knowledge and competence, learning and mastery.